2022
DOI: 10.1002/anie.202205562
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Ruthenium‐Catalyzed Double Remote C(sp2)−H / C(sp3)−H Functionalizations by Radical Relay

Abstract: Distal C(sp 2 )À H and C(sp 3 )À H functionalizations have recently emerged as step-economical tools for molecular synthesis. However, while the C(sp 2 )À C(sp 3 ) construction is of fundamental importance, its formation through double remote C(sp 2 )À H/C(sp 3 )À H activation has proven elusive. By merging the ruthenium-catalyzed meta-C(sp 2 )À H functionalization with an aliphatic hydrogen atom transfer (HAT) process, we, herein, describe the catalyzed twofold remote C(sp 2 )À H/C-(sp 3 )À H functionalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 120 publications
1
11
0
1
Order By: Relevance
“…The reduced regioselectivity might be attributed to the reduced steric bulk of benzene compared with that of p -cymene. Interestingly, replacement of (C 6 H 5 O) 2 P­(O)­OH with sulfonic acids, such as p -TsOH·H 2 O or TfOH, also successfully resulted in regioselective para -alkylation, providing 3a in 87 and 75% yield, respectively, suggesting that (C 6 H 5 O) 2 P­(O)­OH did not serve as a ligand for Ru complexes, as proposed in previous reports, to tune the redox properties of Ru photocatalysts (entries 8–9) . Among other bases, Na 2 CO 3 afforded a similar yield (entry 11).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The reduced regioselectivity might be attributed to the reduced steric bulk of benzene compared with that of p -cymene. Interestingly, replacement of (C 6 H 5 O) 2 P­(O)­OH with sulfonic acids, such as p -TsOH·H 2 O or TfOH, also successfully resulted in regioselective para -alkylation, providing 3a in 87 and 75% yield, respectively, suggesting that (C 6 H 5 O) 2 P­(O)­OH did not serve as a ligand for Ru complexes, as proposed in previous reports, to tune the redox properties of Ru photocatalysts (entries 8–9) . Among other bases, Na 2 CO 3 afforded a similar yield (entry 11).…”
Section: Resultsmentioning
confidence: 69%
“…CV plots at room temperature featured an oxidation peak for [RuCl 2 ( p -cymene)] 2 at 1.06 V, complex A at 0.98 V, and complex A with K 2 CO 3 and (C 6 H 5 O) 2 P­(O)­OH at 0.37 V, indicating that complex A with K 2 CO 3 and (C 6 H 5 O) 2 P­(O)­OH would be a more efficient photocatalytic redox system that can reduce alkyl halides (Figure D). Optimization and kinetic experiments of acids and bases showed that switching the combination of bases and acids reduced the reaction efficiency (for details, see Table S1, entries 7–22, and Section 6.14 in the Supporting Information); thus, K 2 CO 3 and (C 6 H 5 O) 2 P­(O)­OH might serve as regulators for the pH value of the reaction system and tune the redox potential of complex A , in contrast to previous reports . Furthermore, replacing p -cymene in [RuCl 2 ( p -cymene)] 2 with less sterically hindered benzene resulted in decreased regioselectivity, indicating that the steric hindrance of p -cymene in complex A is the key to controlling the regioselectivity (Table , entry 6).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As discussed in the literature, [55][56][57][58] by irradiation with blue light, [59][60][61][62] the Ru(bpy) 3 Cl 2 catalyst can be excited to the S 1 state, being 2.66 eV higher in energy than the S 0 state. After relaxation, it can achieve the T 1 state, with a relative energy of 1.96 eV with respect to the S 0 state as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…In Gegenwart des Phosphinliganden wurde auch das dimethylierte Produkt 3 b nachgewiesen, bei dem sich beide Methylgruppen in ortho ‐Position befanden. Unter Bestrahlung mit sichtbarem Licht, die nachweislich die Dissoziation von p ‐Cymol unterstützt, [6b] konnte die Methylierung direkt mit Methyliodid bei Raumtemperatur durchgeführt werden, wobei selektiv die ortho ‐Produkte 3 a und 3 b entstanden, wenn auch mit einem geringeren Umsatz (Schema S4). Außerdem konnten wir die ortho ‐Selektivität der Reaktionen unter Verwendung von Benzylchloriden mit elektronenspendenden und elektronenziehenden Gruppen erfolgreich vorhersagen (Abbildung 8d).…”
Section: Ergebnisse Und Diskussionunclassified